UJI AKTIVITAS ANTIMIKROBA DAN IDENTIFIKASI EKSTRAK BUAH SAWO MANILA (ACHRAS ZAPOTA L.) TERHADAP BEBERAPA MIKROBA PATOGEN DENGAN METODE DIFUSI AGAR - Mukhriani Mukhriani; Nurlina Nurlina; Fajrul Fhalaq Baso (Universitas Islam Negeri Alauddin Makassar, 2014)
The research has conducted antimicrobial activity assay and identification of sapodilla fruit extract manila (Achras zapota L.) against some pathogenic microbes with agar diffusion method. Manila sapodilla fruit extraction by maceration method by using the solvent ethyl acetate and ethanol 70%. Manila sapodilla fruit has tested by screening extract at a concentration of 1% on the test bacteria which is namely Staphylococcus aureus, Staphylococcus epidermis, Streptococcus mutans, Pseudomonas aeruginosa, Salmonella thyposa, Vibrio sp, Bacillus subtillis, and the fungus is Candida albicans. Furthermore, the inhibition has tested by using the agar diffusion method (paper disc) at a concentratied of 1500ppm, 1000ppm, 500ppm, and 100ppm against screening test results of bacteria. Furthermore, identification of classes of compounds sapodilla fruit of extract phytochemicals by used screening manila methods qualitative.Screening results showed that the antimicrobial activity of the ethanol extract manila sapodilla fruit can inhibit the growth of Staphylococcus aureus, Staphylococcus epidermis, Streptococcus mutans, and Salmonella thyposa. Inhibition test using the agar diffusion method, shows that more the concentration used, more the diameter of the resulting barriers. The results of the identification of sapodilla fruit ethanol extract showed a class of compounds manila tannins, flavonoids, and terpenoids.